Antimicrobial Peptide Octoprohibitin-Encapsulated Chitosan Nanoparticles Enhanced Antibacterial Activity against Acinetobacter baumannii - E. H. T. Thulshan Jayathilaka; Jinwook Han; Mahanama De Zoysa; Ilson Whang (MDPI AG, 2024)
Background: This study focused on evaluating the physiochemical characteristics and antibacterial activity of Octoprohibitin-encapsulated CNPs (Octoprohibitin-CNPs) against Acinetobacter baumannii. Methods: Octoprohibitin was encapsulated into CNPs via ionotropic gelation with carboxymethyl chitosan (CMC) and low molecular weight chitosan (CS). Octoprohibitin-CNPs were dispersed in phosphate-buffered saline and the release kinetic profile was determined. Then Octoprohibitin-CNPs were examined using field-emission transmission electron microscopy and physicochemical characterization was performed. Antibacterial activity of Octoprohibitin-CNPs against A. baumannii was evaluated. Biofilm inhibition and eradication assays were performed using the crystal violet (CV) staining-based method for biofilm quantification. Results: The average diameter, zeta potential, encapsulation efficiency, and loading capacity of Octoprohibitin-CNPs were 244.5 ± 21.97 nm, +48.57 ± 0.38 mV, and 85.7% and 34.2%, respectively. TEM analysis imaging revealed that Octoprohibitin-CNPs are irregularly shaped, with fewer aggregates than CNPs. Octoprohibitin-CNPs exhibited a biphasic release pattern, characterized by an initial rapid phase followed by a sustained release over time, extending up to 93.68 ± 6.48% total release until 96 h. In vitro, Octoprohibitin-CNPs showed lower cytotoxicity compared to Octoprohibitin alone. Time-kill kinetic and bacterial viability reduction assays showed Octoprohibitin-CNPs exhibited slightly higher antibacterial activity against A. baumannii than Octoprohibitin. Conclusions: Octoprohibitin-CNP-treated A. baumannii exhibited higher levels of morphological deviation, increased membrane permeability, and the production of reactive oxygen species, as well as antibiofilm activity with greater biofilm inhibition and eradication than Octoprohibitin. These findings show that Octoprohibitin-CNPs perform better against A. baumannii compared to Octoprohibitin alone.